Femmes de mœurs légères au XVIIe siècle - Charbonneau, Hubert (Mémoires de la Société généalogique canadienne-française, 1996)
Lien avec Montréal – énumération de femmes bannies ou autres pour des moeurs légères. Petite analyse.
issued: 1996-22-00
Keywords: Femmes

De la femme déchue à la femme infectieuse: perception sociale et répression de la prostitution montréalaise pendant la Seconde Guerre mondiale - Commend, Susanne (Université de Montréal, 1996)
Keywords: Femmes; Prostitution

Le travail des femmes a une histoire: l`industrialisation - Lévesque, Andrée (Chroniques féministes, 1996)
issued: 1996-11/1996-12
Keywords: Femmes; Travail

Table ronde. L'histoire des femmes: 25 ans de recherche et d'enseignement - Baillargeon, Denyse (Cahiers d'histoire, 1996)
issued: 1996-21-00
Keywords: Femmes; Histoire

Menstruation Goes Public: Aspects of Women's Menstrual Experience in Montreal, 1920-1975 - Armeni, Elizabeth (Université McGill, 1996)
Keywords: Femmes

Representing Twentieth Century Canadian colonial Identity: the Imperial Order Daughters of the Empire (IODE) - Pickles, Catherine Gillian (Université McGill, 1996)
Keywords: Britanniques; Femmes

Roughing It In Suburbia: Reading Chatelaine Magazine 1950-1969 - Korinek, Valerie Joyce (University of Toronto, 1996)
Keywords: Femmes; Féminisme

'Archi-ettes' in Training: The Admission of Women to McGill's School of Architecture - Adams, Annmarie (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Femmes; Université McGill

Les politiques familiales au Québec. Une perspective historique - Baillargeon, Denyse (Lien social et Politiques, 1996)
issued: 1996-23-00
Keywords: Enfants; Famille; Femmes

'If You Had no Money, You Had no Trouble, Did You?' Montréal Working-Class Housewives during the Great Depression - Baillargeon, Denyse (Canadian Women. A Reader, 1996)
Keywords: Crise; Famille; Femmes

Women in Montreal during Three Wars: an Examination of Gender, Nationalism and Colonialism - Pickles, Katie (Université McGill, 1996)
Keywords: Femmes; Guerre; Nationalisme

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Trabajo Asalariado, género e identidad: la inserción de las Mujeres Colombianas en Montreal - Osorio Ramírez, Amantina Maria (Université de Montréal, 1996)
Keywords: Colombiens; Femmes; Travail

Criminal Women and Bad Girls: Regulation and Punishment in Montreal, 1890-1930 - Myers, Tamara (Université McGill, 1996)
Keywords: Criminalité; Délinquance; Femmes; Prisons

Antiracism organizing and resistance in nursing : African Canadian Women - Calliste, Agnes (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1996)
Number: 3
Keywords: Africains; Femmes; Infirmières; Noirs

Housing of Female Single-Parent Families with Special Reference to Point St. Charles - Bourianova, Ioulia (Université McGill, 1996)
Keywords: Femmes; Logement; Pointe-Saint-Charles; Quartiers

Fréquenter les Gouttes de lait: l'expérience des mères montréalaises, 1910-1965 - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1996)
Number: 1
Keywords: Enfants; Femmes; Goutte de lait; Mortalité

Étude du processus de construction du sens dans les médias: le cas de la tragédie de l'École polytechnique en 1989 - Boudreau, Julie (Université de Sherbrooke, 1996)
Keywords: Devoir (Le); Femmes; Montreal Gazette; Presse (La); École polytechnique